-17-6w-13=-6w-11

Simple and best practice solution for -17-6w-13=-6w-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17-6w-13=-6w-11 equation:



-17-6w-13=-6w-11
We move all terms to the left:
-17-6w-13-(-6w-11)=0
We add all the numbers together, and all the variables
-6w-(-6w-11)-30=0
We get rid of parentheses
-6w+6w+11-30=0
We add all the numbers together, and all the variables
-19!=0
There is no solution for this equation

See similar equations:

| X=3z-100 | | -9(x+3)=-9x-27 | | 10.16-3j=18.26 | | 16k+20+8=13k-20 | | -2.5(3x+4)=32.5 | | -(7y-9)=2×(9-5y)-3 | | (4/9)^3x=243/32 | | −7(-10+9)=37+3x-10 | | -9(x-3)=-9x-27 | | 8.44=(34.6+4h/5 | | 16=4j+8 | | 6x-4(-3x-4)=-20 | | 2^(2x-3)=32 | | (12n+8)=-39 | | 14=u+8 | | 3(7x+4/7)=-576/7 | | –4g−15=–5g | | 3r-8=-5r+12 | | 21+g=124.63 | | -6x-3(2x-4)=-24 | | 25=b+15 | | 6-2h=-2 | | 7(-8+5x)=14 | | −7(s+9)=37+3s | | 2^2x-1=6 | | 2x+4(x-3)=6 | | -3(1x+1)=-9/2 | | k/42=7 | | -164-14x=76-2x | | 4^x+2=32^x | | 6x-5=2x+-7 | | 4.5x+15=7x+12.5 |

Equations solver categories